Are inhaled corticosteroids associated with an increased risk of fracture in children? - van Staa, T; Bishop, N; Leufkens, H; Cooper, C (2004)
Inhaled corticosteroids are widely used in the long-term management of asthma in children. Data on the relationship between inhaled corticosteroid therapy and osteoporotic fracture are inconsistent. We address this issue in a large population-based cohort of children aged 4-17 years in the UK (the General Practice Research Database). The incidence rates of fracture among children aged 4-17 years taking inhaled corticosteroids (n=97,387), taking bronchodilators only (n=70 984) and a reference group (n=345,758) were estimated. Each child with a non-vertebral fracture (n=23,984) was subsequently matched by age, sex, practice, and calendar time to one child without a fracture. Fracture incidence was increased in children using inhaled corticosteroids, as well as in those receiving bronchodilators alone. With an average daily beclomethasone dose of 200 microg or less, the crude fracture risk relative to nonusers was 1.10 [95% confidence interval (CI), 0.96-1.26]; with dosage of 201-400 microg, it was 1.23 (95% CI, 1.08-1.39); and with dosages over 400 microg, it was 1.36 (95% CI, 1.11-1.67). This excess risk disappeared after adjustment for indicators of asthma severity. The increased risk of fracture associated with use of inhaled corticosteroids is likely to be the result of the underlying illness, rather than being directly attributable to inhaled corticosteroid therapy.